ChREBP-Mediated Regulation of Lipid Metabolism: Involvement of the Gut Microbiota, Liver, and Adipose Tissue - Iizuka, Katsumi; Takao, Ken; Yabe, Daisuke (Frontiers in Endocrinology, 2020)
Carbohydrate response element binding protein (ChREBP) plays an important role in development of type 2 diabetes, dyslipidemia and non-alcoholic fatty liver disease as well as tumorigenesis. ChREBP is highly expressed in lipogenic organs such as liver, intestine and adipose tissue, in which it regulates production of acetyl CoA from glucose by inducing Pklr and Acyl expression. It has been recently demonstrated that ChREBP plays a role in conversion of gut microbiota-derived acetate to acetyl CoA by activating its target, Acss2, in liver. ChREBP regulates fatty acid synthesis, elongation and desaturation by inducing Acc1 and Fasn, Elovl6 and Scd1 expression, respectively. ChREBP also regulates formation of very low-density lipoproteins by inducing expression of Mttp. Furthermore, ChREBP plays a crucial role in peripheral lipid metabolism by inducing Fgf21 expression as well as Angptl3 and Angptl8, which are known to suppress peripheral lipoprotein lipase activity. In addition, ChREBP is involved in production of palmitic-acid-5-hydroxystearic-acids, which increase insulin sensitivity in adipose tissue. Curiously, ChREBP is indirectly involved in fatty acid β-oxidation and the consequent ketogenesis. Thus, ChREBP regulates whole body lipid metabolism by controlling the transcription of lipogenic enzymes and liver-derived cytokines.